The Competence of Health Workers in the Early Detection of Neonatal at the Puskesmas Ulee Kareng, Banda Aceh - Dewi Marianthi; Teuku Alamsyah (Universitas Teuku Umar, 2020)
Infant mortality rate in Indonesia is quite high, and newborns have an even higher mortality rate compared to toodlesr or older infants. The competence of the health workers in identifying early detection of newborns at risk in the communit considered as one of the factors that generates belated treatment in the health services. To increase the competence of health workers in early detection of newborns at risk by providing training for neonatal care. A quasi-experimental quantitative method, with one-group pretest-posttest design. The sample of the research is 45 health workers in Ulee Kareng Health Center, Banda Aceh. The result of the research revealed the increased competence in knowledge, attitudes and skills of the health workers with p value 0,0000 before and after the neonatal care training. Neonatal care training will increase the competence (knowledge, attitudes and skills) of health workers in early detection of newborns at risk.